MAL regulates clathrin-mediated endocytosis at the apical surface of Madin–Darby canine kidney cells - Martín-Belmonte, Fernando (The Rockefeller University Press, 2003)
MAL is an integral protein component of the machinery for apical transport in epithelial Madin–Darby canine kidney (MDCK) cells. To maintain its distribution, MAL cycles continuously between the plasma membrane and the Golgi complex. The clathrin-mediated route for apical internalization is known to differ from that at the basolateral surface. Herein, we report that MAL depends on the clathrin pathway for apical internalization. Apically internalized polymeric Ig receptor (pIgR), which uses clathrin for endocytosis, colocalized with internalized MAL in the same apical vesicles. Time-lapse confocal microscopic analysis revealed cotransport of pIgR and MAL in the same endocytic structures. Immunoelectron microscopic analysis evidenced colabeling of MAL with apically labeled pIgR in pits and clathrin-coated vesicles. Apical internalization of pIgR was abrogated in cells with reduced levels of MAL, whereas this did not occur either with its basolateral entry or the apical internalization of glycosylphosphatidylinositol-anchored proteins, which does not involve clathrin. Therefore, MAL is critical for efficient clathrin-mediated endocytosis at the apical surface in MDCK cells.